HUBUNGAN USIA, ULTRAFILTRATION RATE (UFR), INTERDIALYTIC WEIGHT GAIN (IDWG), DAN DIABETES MELITUS DENGAN KEJADIAN HIPOTENSI INTRADIALITIK PADA PASIEN GAGAL GINJAK KRONIK DI RSUD DR. H. ABDUL MOELOEK PROVINSI LAMPUNG - Nurfatin, Ghina Nisrina; Yonata, Ade (CV. Jasa Sukses Abadi, 2026)
Chronic kidney disease is a clinical syndrome due to changes in kidney’s function or structure with management by hemodialysis. The complication of hemodialysis is intradialytic hypotension, whose incidence is influenced by several factors. The study aims to determine the correlation between age, Ultrafiltration Rate (UFR), Interdialytic Weight Gain (IDWG), and diabetes mellitus with the incidence of intradialytic hypotension. The study is an analytic observational study with cross-sectional design at the hemodialysis installation of RSUD Dr. H. Abdul Moeloek in December 2022 - January 2023 using primary data from 72 patients. Data analysis using the Chi-Square test and multiple logistic regression. Most of the respondents were female (56.9%), ≤65 years old (83.3%), had UFR >10 ml/KgBB/H (59.7%), IDWG of >3 kg (37.5%), history of diabetes mellitus (55.6%) , intradialytic hypotension (58.3%), and the most blood pressure reduction occurred in the 1st hour. There was no correlation between patient’s age (p=0.200) and intradialytic hypotension but there were a correlation between UFR (ml) (p=0.000), IDWG (kg) (p=0.000), and a history of diabetes mellitus (p=0.000) with intradialytic hypotension. Ultrafiltration Rate has an effect of 20.744 times on intradialytic hypotension. There was a correlation between UFR (ml), IDWG (kg), and diabetes mellitus with the incidence of intradialytic hypotension in patients with chronic renal failure. Ultrafiltration Rate (UFR) has the most impact on the incidence of intradialytic hypotension at RSUD dr. H. Abdul Moeloek Lampung.